-2h-7=7h-4h

Simple and best practice solution for -2h-7=7h-4h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2h-7=7h-4h equation:



-2h-7=7h-4h
We move all terms to the left:
-2h-7-(7h-4h)=0
We add all the numbers together, and all the variables
-2h-(+3h)-7=0
We get rid of parentheses
-2h-3h-7=0
We add all the numbers together, and all the variables
-5h-7=0
We move all terms containing h to the left, all other terms to the right
-5h=7
h=7/-5
h=-1+2/5

See similar equations:

| 23y=14 | | 4^2x-5-5=64 | | x/27=5+3(2x-4)+10 | | 2x+15=5x-35 | | 2y=-9+3y | | -10k=10-8k | | 5x+6x+4x=360 | | |10x-8|=-38 | | 4+24=-4(6x-7) | | 3.7=10+5m | | 7+9d=7d-5 | | 10(b-5)+18=-72 | | 3(8+4x)=3(2x-8) | | v-36/7=8 | | 7v=20 | | |10x-8|=38 | | 2-5u=-7u | | 9-6x=2x-15 | | 4b-25=51 | | -10m-1=-9m+8 | | 2.5x-12=180 | | 2(2+p)-3=7 | | x+40+x+x-10=360 | | -8x+5=-2(4x+3) | | r/3-(-2)=3 | | -15+9p=-60 | | 10^0.3=1/x | | 5(2n-)-(n+8)=13 | | 3j-7=-1 | | 28=38-2x | | X-+4(2x+2)=35 | | 7x-4=-9x+8 |

Equations solver categories